Peningkatan Kapasitas Pemasaran Petani Melalui Pelatihan Komunikasi Bisnis di Desa Guci Kabupaten Tegal - Budiyoko, Budiyoko; Dharmawan, Budi; Satriani, Ratna Ekawati; Widyarini, Indah (Participative Journal: Jurnal Pengabdian Pada Masyarakat, 2025)
Enhancing farmers' marketing capacity in rural areas has become crucial in facing the increasingly dynamic market competition. This community service activity, in the form of business communication training, is aimed at improving farmers' ability to market their agricultural products. The training sessions were designed to deliver fundamental business communication techniques, public speaking skills, and digital marketing strategies, followed by role-play activities to practice communication and public speaking. Vegetable farmers in Guci Village, Tegal District, who participated in the training, demonstrated high enthusiasm throughout the event. During the role-play sessions, it was observed that the farmers' confidence and communication skills in public speaking improved. This initiative is expected to significantly contribute to enhancing farmers' capacity and the effectiveness of agricultural product marketing in Guci Village, while also optimizing the use of digital technologies to increase their competitiveness in an increasingly complex market